Urgensi Pendidikan Kewarganegaraan di Sekolah Dasar dalam Menghadapi Era Masyarakat 5.0 - Meliana Lalita Putri; Dinie Anggraeni Dewi (Journal on Education, 2021)
The phenomenon at this time we often find children no longer respect parents, anti-social attitudes that appear from everyday life both at school and society. In global competition, a nation needs to be an innovative nation to become a superior nation. especially in facing the next 5.0 society era. Then the need for a strong order of values and policies so that the crisis of culture and national disintegration does not occur in Indonesia. Education in Indonesia must instill national character and spirit originating from the nation's cultural roots and based on Pancasila as the basis of country, philosophy, and noble values. Through, citizenship education learning is expected to be a solution in fostering citizens who have social awareness.